Light-regulated microRNAs shape dynamic gene expression in the zebrafish circadian clock. - Zuo Wang; Shuang Wang; Yi Bi; Alessandra Boiti; Shengxiang Zhang; Daniela Vallone; Xianyong Lan; Nicholas S Foulkes; Haiyu Zhao (PLoS Genetics)
A key property of the circadian clock is that it is reset by light to remain synchronized with the day-night cycle. An attractive model to explore light input to the circadian clock in vertebrates is the zebrafish. Circadian clocks in zebrafish peripheral tissues and even zebrafish-derived cell lines are entrainable by direct light exposure thus providing unique insight into the function and evolution of light regulatory pathways. Our previous work has revealed that light-induced gene transcription is a key step in the entrainment of the circadian clock as well as enabling the more general adaptation of zebrafish cells to sunlight exposure. However, considerable evidence points to post-transcriptional regulatory mechanisms, notably microRNAs (miRNAs), playing an essential role in shaping dynamic changes in mRNA levels. Therefore, does light directly impact the function of miRNAs? Are there light-regulated miRNAs and if so, which classes of mRNA do they target? To address these questions, we performed a complete sequencing analysis of light-induced changes in the zebrafish transcriptome, encompassing small non-coding RNAs as well as mRNAs. Importantly, we identified sets of light-regulated miRNAs, with many regulatory targets representing light-inducible mRNAs including circadian clock genes and genes involved in redox homeostasis. We subsequently focused on the light-responsive miR-204-3-3p and miR-430a-3p which are predicted to regulate the expression of cryptochrome genes (cry1a and cry1b). Luciferase reporter assays validated the target binding of miR-204-3-3p and miR-430a-3p to the 3'UTRs of cry1a and cry1b, respectively. Furthermore, treatment with mimics and inhibitors of these two miRNAs significantly affected the dynamic expression of their target genes but also other core clock components (clock1a, bmal1b, per1b, per2, per3), as well as the rhythmic locomotor activity of zebrafish larvae. Thus, our identification of light-responsive miRNAs reveals new intricacy in the multi-level regulation of the circadian clockwork by light.